(untitled) (Eurasian Journal of Ecology, 2016)
Study of the body shape in imago of Pyrrhocoris apterus L. from the control (botanic reserve) and the impact (city Park in Alekseevka town) populations by the methods of geometric morphometrics had established, that the anthropogenic factors (the urbanization) affected the range of morphological variability in more extent than the season ones. At the beginning and in the middle of summer in the impact urban population an imago’s growth was notably suppressed and their body sizes (as it may be estimated by centroid sizes) were significantly less, than in the control population. Males and females differed significantly only in the control group. Seasonal changes of the imago’s body shape were parallel in the two comparing localities (control and impact ones) and similar in their range. Differentiation between urban and control groups was permanent through various seasons. Studied aspects of variability of body shape can be ranged in accordance with their effects (in descending order): anthropogenic, seasonal, and sexual.